Review of financials, sales, and marketing strategy for micro, small, and medium enterprises in Palangka Raya City - Giovanni, Jonathan; Subianto, Pratiwi; Pungan, Yudi (Fakultas Ekonomi dan Bisnis Universitas Palangka Raya, 2024)
This academic investigation is meticulously designed with the primary objective of categorizing and analyzing the performance metrics of Micro, Small, and Medium Enterprises (MSMEs) situated within the urban confines of Palangka Raya City, with a particular emphasis on financial dimensions, product sales figures, and the efficacy of marketing strategies employed by these enterprises. Through the utilization of this systematic methodology, it becomes feasible to discern and identify groups of MSMEs that exhibit homogeneity in their operational characteristics, thereby facilitating the development of more precise and tailored strategies aimed at fostering their growth and development. To gather relevant primary data that would underpin this analysis, a comprehensive survey was administered to a total of 100 respondents, utilizing a well-structured questionnaire designed to elicit detailed information regarding their business operations. The analytical process employed in this study incorporated descriptive statistical tests, which were instrumental in not only processing the collected data but also in effectively visualizing the results, thus enhancing the interpretability of the findings. The outcomes derived from the clustering analysis revealed significant patterns that can be leveraged to inform management strategies for MSMEs, particularly in relation to enhancing operational efficiency and augmenting the effectiveness of their marketing endeavors. It is the aspiration of this scholarly work that the insights garnered herein will serve as a valuable resource for government entities and various stakeholders, enabling them to make informed decisions that are grounded in empirical data and that contribute positively to the economic growth of the local community. Furthermore, by providing a clearer understanding of the operational landscape of MSMEs, this study aims to encourage the implementation of supportive policies that are conducive to sustainable development within the region. Ultimately, the research endeavors to bridge the gap between academic inquiry and practical application, thereby fostering a collaborative environment in which both theory and practice can thrive in the pursuit of economic advancement. In conclusion, the findings of this study hold the potential to significantly influence the strategic direction of MSMEs in Palangka Raya City, ultimately contributing to a more robust local economy.